A Remark on multivalently convex and starlike functions - Nunokawa, Mamoru; Owa, Shigeyoshi; Yavuz Duman, Emel; POLATOĞLU, YAŞAR (My University, 2007)
Applying the result for certain analytic functions due to M. Nunokawa [Proc. Japan Acad. 68A, 152–153 (1992; Zbl 0773.30020)], some properties for multivalently convex and starlike functions ar discussed.
Keywords: Multivalently starlike; multivalently convex